Integrating network pharmacology, UPLC-Q-TOF-MS and molecular docking to investigate the effect and mechanism of Chuanxiong Renshen decoction against Alzheimer's disease - Zhuo Jun Shen; Yun Bo Fu; Jin Ling Hou; Lu Ning Lin; Xiao Yan Wang; Chang Yu Li; Yuan Xiao Yang (BMC, 2022)
Abstract Background and aim Chuanxiong Renshen decoction (CRD) is a traditional Chinese medicine compound used to treat Alzheimer's disease (AD). However, the effects and active ingredients of CRD and its mechanism have not been clarified. We aimed to determine the neuroprotective effects of CRD in a triple-transgenic mouse model of AD (3 × Tg-AD) and investigate the possible active ingredients and their mechanisms. Methods Morris water maze (MWM) tests were used to determine the protective effect of CRD on learning and memory ability. Afterward, we used brain tissue staining, immunofluorescent staining and western blotting to detect the neuroprotective effects of CRD. Ultraperformance liquid-chromatography-quadrupole-time-of-flight tandem mass spectrometry (UPLC-Q-TOF-MS) was applied to determine the ingredients of CRD, and the potential AD targets were obtained from DisGeNET and the GeneCards database. The protein‒protein interaction (PPI) network was built with the additional use of STRING 11.0. Metascape was used in the pathway enrichment analysis. Discovery Studio 2016 (DS) software was used to analyze the binding ability of CRD and AD-related genes. Finally, we verified the regulatory effect of CRD on the predicted core targets EGFR and CASP3 by western blotting. Results Our study indicated that CRD can significantly improve learning and memory, reduce the expression of Aβ and protect neurons. A total of 95 ingredients were identified in the CRD. Then, 25 ingredients were identified in serum, and 5 ingredients were identified in the brain tissue homogenate. PPI network analysis identified CASP3, EGFR, APP, CNR1, HIF1A, PTGS2 and MTOR as hub targets. KEGG and GO analyses revealed that the TNF signaling pathway and MAPK signaling pathway were enriched in multiple targets. The results of molecular docking proved that the binding of the ingredients with potential key targets was excellent. The western blotting results showed that CRD could significantly reduce the expression of CASP3 and EGFR in the hippocampus of 3 × Tg-AD mice. Combined with literature analysis, we assumed the neuroprotective effect of CRD on AD may occur through regulation of the MAPK signaling pathway. Conclusion CRD significantly alleviated injury in 3 × Tg-AD mice. The possible active ingredients are ferulic acid, rutin, ginsenoside Rg1 and panaxydol. The therapeutic effect of CRD on AD is achieved through the downregulation of CASP3 and EGFR. The neuroprotective effect of CRD on AD may occur through regulation of the MAPK signaling pathway.